Postoperative Complication With Obstructive Sleep Apnea - Sheikh, Zubair Ahmad; Sripathi Sowmya Priya (Jurnal Kebidanan Manna, 2024)
Obstructive Sleep Apnea (OSA) is a common disorder defined by recurrent episodes of upper airway obstruction during sleep, resulting in intermittent hypoxia, hypercapnia, and disrupted sleep patterns. Patients with obstructive sleep apnea (OSA) encounter increased risks of postoperative complications in surgical contexts, such as respiratory problems, cardiovascular incidents, and extended recovery durations. The perioperative management of patients with obstructive sleep apnea (OSA) poses distinct challenges for anesthesiologists and surgeons, primarily due to risks of airway obstruction, heightened opioid sensitivity, and associated comorbidities like hypertension and obesity. Postoperative complications are significant, as the sedative effects of anesthesia and analgesics heighten airway collapsibility, thereby increasing the risk of hypoxemia and apneic events. This review examines the range of postoperative complications linked to obstructive sleep apnea, emphasizing respiratory issues, cardiovascular instability, and the likelihood of extended hospitalization. It also delineates contemporary strategies for the perioperative management of patients with obstructive sleep apnea, encompassing preoperative screening, intraoperative monitoring, and postoperative care. The role of continuous positive airway pressure (CPAP) therapy, opioid-sparing analgesic techniques, and the necessity for individualized anesthesia plans to reduce risks is emphasized. Comprehending these management strategies is crucial for enhancing patient outcomes and decreasing the occurrence of postoperative complications in individuals with OSA.